(untitled) (European Journal of Education and Psychology, 2018)
A study was designed with the aim of identifying different profiles of emotional regulation in a sample of university students, and analysing the differences among the identified profiles in relation to stressors perception and psychophysiological stress responses. The participants were 504 Spanish physiotherapy students (74% women), with a mean age of 21.06 ± 3.74 years old, which answered the Difficulty Emotion Regulation Scale (DERS) and the Academic Stress Questionnaire (stressors scale [ECEA] and response scale [RCEA]). Based on Cluster analysis, three emotional regulation profiles were identified: students with high emotional regulation profile, students with low emotional regulation profile and students with low emotional regulation but high scores in emotional attention profile. The results indicated statistically significant differences between the emotional regulation profiles in stress appraisals and psychophysiological responses. Succinctly, students with high emotional regulation profile perceived academic environment as less threatening and showed lesser scores in stress responses. Students with low emotional regulation profile and low emotional regulation but high emotional attention profile showed similar scores, with the exception of sleep disorders. Briefly, physiotherapy students who had higher scores on emotional control and acceptance, perceived the academic setting in a more adaptive way and reported fewer stress responses.